Evaluasi Kesesuaian Penggunaan Antbiotik pada Pasien dengan Infeksi Methicillin Resistant Staphylococcus Aureus (MRSA) di RSUD. Dr. Moewardi Surakarta - Tristina Devi Azzahra; Titik Nuryastuti; Ika Puspitasari (Majalah Farmaseutik, 2021)
MRSA is one of the Multi Drug Resistant Organism (MDRO) with a high number of cases and problem. Incidence of MRSA in Indonesia is quite significant every years. In 1986 there were 2.5%, 1993 increased to 9.4% and in 2006 23.5%. The problem is methicillin is no longer effective and other antibiotics vary in efficacy. The aims of this reasearch was to evaluate the used of antibiotics in patients with MRSA infection in Dr. Moewardi Hospital in Surakarta. The study was performed using retrospective Cohort study to examine the relationship between suitability antibiotic to clinical outcomes in patients with MRSA infection in Dr. Moewardi Hospital in Surakarta during period 1 January 2017 - 31 December 2018. The evaluation was conducted to the suitability of type, dose, frequency, duration of antibiotic use and pharmacokinetic profile. Chi-square test was used to analyse the relationship of antibiotic suitability to clinical outcomes including predicted pharmacokinetic parameters for clinical outcomes.There were 28 samples with MRSA infection tested in this study. Twenty one patients (75%) used appropriate antibiotics showed good clinical outcome 21 patients (85,7%) and 7 patients (25%) with unsuitable antibiotics showed good clinical outcome 71,4%.Keywords: antibiotic, clinical outcome, pharmacokinetic, MRSA.